Serum apoptotic caspase activity in chronic hepatitis C and nonalcoholic Fatty liver disease - Papatheodoridis, George V; Hadziyannis, Emilia; Tsochatzis, Emmanuel; Georgiou, Anastasia; Kafiri, Georgia; Tiniakos, Dina G; Margariti, Katerina; Manolakopoulos, Spilios; Manesis, Emanuel K; Archimandritis, Athanasios J (Journal of clinical gastroenterology, 2010)
Apoptotic caspases are substantially activated in liver and serum caspase activity has been suggested as a marker of early liver injury. To investigate whether serum levels of caspase-generated fragments of cytokeratin-18 are associated with the severity of histologic lesions in chronic hepatitis C virus (HCV) infection and nonalcoholic fatty liver disease (NAFLD). We included 134 patients with chronic HCV infection and 58 patients with NAFLD, who consecutively underwent liver biopsy, and 40 healthy controls. Caspase-generated cytokeratin-18 fragment levels were blindly measured in stored serum samples. Median cytokeratin-18 fragment levels were lower in HCV-positive patients with minimal/mild than patients with moderate/severe histologic lesions (174 U/L vs. 223 U/L, P<0.001) offering moderate accuracy for differentiation between the 2 groups (c-statistic: 0.74). Cytokeratin-18 fragments levels were lower in healthy subjects (148 U/L) than patients with simple fatty liver (174 U/L, P=0.013) than patients with nonalcoholic steatohepatitis (355 U/L, P<0.001) offering excellent diagnostic accuracy for differentiation between the 2 latter groups (c-statistic: 0.87). Serum apoptotic caspase activity is associated with the severity of liver histologic lesions in both chronic HCV infection and NAFLD, but it has excellent diagnostic accuracy in NAFLD and moderate accuracy in chronic HCV patients.